2023
DOI: 10.3390/nu15051298
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis: Malnutrition and In-Hospital Death in Adults Hospitalized with COVID-19

Abstract: Background: Malnutrition and increased malnutrition risk are frequently identified in hospitalized adults. The increase in hospitalization rates during the COVID-19 pandemic was accompanied by the documentation of adverse hospitalization outcomes in the presence of certain co-morbidities, including obesity and type 2 diabetes. It was not clear whether the presence of malnutrition increased in-hospital death in patients hospitalized with COVID-19. Objectives: To estimate the effect of malnutrition on in-hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…Consistent with previous studies, malnutrition amplifies the severity of infectious diseases, including COVID-19 [3,12,[40][41][42][43][44]. A meta-analysis of 12 studies demonstrated a similar trend, showing that malnourished patients had significantly higher odds of inhospital mortality (odds ratio = 3.43, 95% CI: 2.55-4.60) during a 90-day follow-up [45].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Consistent with previous studies, malnutrition amplifies the severity of infectious diseases, including COVID-19 [3,12,[40][41][42][43][44]. A meta-analysis of 12 studies demonstrated a similar trend, showing that malnourished patients had significantly higher odds of inhospital mortality (odds ratio = 3.43, 95% CI: 2.55-4.60) during a 90-day follow-up [45].…”
Section: Discussionsupporting
confidence: 85%
“…Consistent with previous studies, malnutrition amplifies the severity of infectious diseases, including COVID-19 [ 3 , 12 , 40 , 41 , 42 , 43 , 44 ]. A meta-analysis of 12 studies demonstrated a similar trend, showing that malnourished patients had significantly higher odds of in-hospital mortality (odds ratio = 3.43, 95% CI: 2.55–4.60) during a 90-day follow-up [ 45 ]. Our study builds on these findings by including non-hospitalized patients and extending the follow-up duration, thus providing a more comprehensive view of the impact of malnutrition on COVID-19 outcomes in various settings.…”
Section: Discussionmentioning
confidence: 94%
“…Many studies suggest also that frailty is related to the hospitalization rate, severity, mortality rate, and LOS [ 5 , 21 23 ]. The higher incidence of malnutrition in hospitalized patients is an ominous sign of poor prognosis [ 24 27 ]. In addition, the invasion of the SARS-CoV-2 into peripheral nerves can lead to loss of smell, impaired sensory function of the oropharynx, swallowing disorders, and an increased risk of death [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Estudios han encontrado que la edad del paciente es un factor que puede influenciar en el grado de desnutrición una vez que estos han sido hospitalizados (Behiry & Salem, 2019;González-Franco et al, 2020;Lovera Montilla & Cáceres Villota, 2023). Mientras más edad presente el paciente, el riesgo de desnutrición aumenta y por tanto también aumenta el riesgo de fallecer (Bhirommuang et al, 2019;Boaz & Kaufman-Shriqui, 2023;Koroušić Seljak et al, 2020;Pereira et al, 2021;Ting et al, 2019) sobre todo con afectaciones como el COVID 19 (Velázquez Alva et al, 2021) y enfermedades renales (Sánchez-Tocino et al, 2022). En el caso de los pacientes oncológicos hospitalizados, no hubo diferencias respecto a las edades, sin embargo presentan las tasas más elevadas de desnutrición hospitalaria (Chimera-Khombe et al, 2022).…”
Section: Resultsunclassified